Efficacy and Safety of Dapagliflozin in Heart Failure With Mildly Reduced or Preserved Ejection Fraction According to Age: The DELIVER Trial. (27th August 2022) - Peikert, Alexander; Martinez, Felipe A.; Vaduganathan, Muthiah; Claggett, Brian L.; Kulac, Ian J.; Desai, Akshay S.; Jhund, Pardeep S.; de Boer, Rudolf A.; DeMets, David; Hernandez, Adrian F.; Inzucchi, Silvio E.; Kosiborod, Mikhail N.; et al.
Abstract : Background: The prevalence of heart failure with mildly reduced or preserved ejection fraction markedly increases with age, with older individuals disproportionately facing excess risk for mortality and hospitalization. Methods: The DELIVER trial (Dapagliflozin Evaluation to Improve the Lives of Patients With Preserved Ejection Fraction Heart Failure) randomized patients with New York Heart Association functional class II–IV and left ventricular ejection fraction >40% to either dapagliflozin or placebo for a median follow-up period of 2.3 years. We examined efficacy and safety outcomes by age categories (<55, 55–64, 65–74, and ≥75 years) and across age as a continuous measure. Results: Among 6263 randomized patients (aged 40–99 years, mean age 71.7±9.6 years), 338 (5.4%) were <55 years, 1007 (16.1%) were 55–64 years, 2326 (37.1%) were 65 to 74 years, and 2592 (41.4%) were ≥75 years. Dapagliflozin reduced the risk of the primary composite outcome compared with placebo in all age categories ( P interaction =0.95) and across the age spectrum as a continuous function ( P interaction =0.76). Similar benefits were observed for the components of the primary outcome, with no significant interaction between randomized treatment and age category. Adverse events occurred more frequently with increasing age, but there were no significant differences in predefined safety outcomes between patients randomized to dapagliflozin and placebo across all age categories. Conclusions: In patients with heart failure and mildly reduced or preserved ejection fraction enrolled in DELIVER, dapagliflozin reduced the combined risk of cardiovascular death or worsening heart failure events across the spectrum of age, with a consistent safety profile, including among the traditionally under-treated older segment of patients ≥75 years. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03619213.